Novel ssDNA aptamer-based fluorescence sensor for perfluorooctanoic acid detection in water - Junyoung Park (Elsevier, 2022)
Per- and polyfluoroalkyl substances (PFAS) are widely detected environmental contaminants, and there is a great need for development of sensor technologies for rapid and continuous monitoring of PFAS. In this study, we have developed fluorescence based aptasensor that can possibly monitor perfluorooctanoic acid (PFOA) in water with limit of detection (LOD) of 0.17 μM. This is first to report the successful isolation of PFAS binding ssDNA aptamers. The obtained aptamer selectively binds PFOA with dissociation constant (KD) of 5.5 μM. Specific aptamer binding sites to PFOA were identified and the length of the fluorinated carbons was a key binding factor rather than the functional group. The aptamer binding to structurally similar PFAS compounds (i.e., perfluorocarboxylic acids and perfluorosulfonic acids with 4–8 carbon chains) was also investigated; the aptamer KD values were 6.5 and 3.3 μM for perfluoroheptanoic acid and perfluorohexanesulfonic acid, respectively, while other analogs did not bind to the aptamer. The presence of major inorganic ions and dissolved organic matter had negligible influences on the aptamer performance (<14% at a 10 mM concentration), and the aptamer performance was also robust in real wastewater effluent conditions, with a KD of 7.4 μM for PFOA. Fluorescence-based aptasensor developed in this study is adequate in monitoring PFOA levels in water contaminated with the accident spills and heavy usage of fire-fighting foams near the industrial sites and military bases. More importantly, the study opens up new capability of aptasensors to efficiently monitor the trace amount of various PFAS compounds and other fluorinated alternatives in natural and engineered water environments.